Ultrashort field emission in metallic nanostructures and low-dimensional carbon materials - Park, D. J.; Ahn, Y. H. (Advances in Physics: X, 2020)
This study investigates recent advances in photoelectron emission generated by irradiating ultrashort lasers on metallic nanostructures and low-dimensional carbon materials. Recently, primary focus has been on improving the efficiency of emitters, i.e. increasing the number of field-emitted electrons and their respective kinetic energies. An example of this is the modification of the conventional metal nanotip through adiabatic nanofocusing and various plasmonic metal structures, such as nanorods and bowtie antenna. The coherent emission control with two color irradiation enabled modulation in the emission yield. In addition, THz waves near the metallic nanostructure induced a highly accelerated, monochromatic energy. Alternative to metallic nanotips, carbon nanotubes are emerging as efficient photoelectron emitters, due to the large enhancement factor associated with their high aspect ratio and damage threshold. They particularly allowed the use of femtosecond light sources with a relatively short wavelength, resulting in the generation of photoelectrons with a narrow bandwidth. Additionally, electronic control over the single-walled nanotubes band structure added a degree of freedom for controlling the electron emission yield. Finally, we review the strong-field tunneling emission in graphene edge, with the emission yield showing an anomalous increase of nonlinear order, corresponding to the deep strong tunneling regime.
Keywords: carbon nanostructures; Photoionization; ultrafast processes